Addressing Food Insecurity in Sub‐Saharan Africa: The Role of Cash Transfers. Issue 4 (11th December 2018) - Burchi, Francesco; Scarlato, Margherita; d'Agostino, Giorgio
Abstract : Food insecurity is one of the international community's priorities in sub‐Saharan Africa (SSA). This article investigates the role played by cash transfers (CTs), the social protection scheme with the largest coverage, in enhancing food security in this region. First, it offers an innovative conceptual framework for explaining the channels through which CT programs can affect food security. Second, based on this conceptual framework, it provides a comprehensive review of evidence of the effects of CTs on different components/indicators of food security in low‐income countries in SSA. The article shows that CTs offer great potential for reducing monetary poverty and enhancing households' access to food, as long as they take full account of important aspects related to their design and implementation. On the other hand, CTs alone cannot influence nutrition knowledge and practice, and are proved to have limited or no effects on food security outcomes, such as diet diversification or child anthropometrics. In order to enhance all the different aspects of food security in the medium to long term, CTs should be integrated with other, social and economic, interventions.